THE EFFECT OF INTERNAL CONTROL SYSTEM ON ORGANIZATIONAL PERFORMANCE THROUGH PERFORMANCE MEASUREMENT SYSTEM IN THE PUBLIC SECTOR - Andi Fitah Ayu Trisnawati; Anisa Kusumawardani; Hariman Bone (SOSIOEDUKASI, 2025)
This study investigates the influence of the internal control system on the organizational performance of regional government institutions, with the performance measurement system functioning as a mediating variable. The research was conducted at the Samarinda City Health Office, involving 190 employees selected through a purposive sampling technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of WarpPLS version 8. The results show that the internal control system has a positive and significant effect on both the performance measurement system and organizational performance. The performance measurement system also demonstrates a positive and significant influence on organizational performance. Moreover, the performance measurement system was found to partially mediate the relationship between the internal control system and organizational performance. These findings highlight the critical role of strong internal control practices in improving the accuracy and reliability of performance measurements, which ultimately enhance organizational performance in public sector institutions. The study contributes to strengthening governance practices, particularly in regional government entities managing essential public services.